Becoming a supply chain leader : mastering and executing the fundamentals - Datta, Sourya (Productivity Press, 2021)
The book explains how to emerge and grow as a supply chain leader and details supply chain and procurement processes and operational activities in real-work scenarios across multiple supply chain verticals. The book defines what an entry-level supply chain professional must do to excel in various types of supply chain verticals such as IT, electronics manufacturing, pharmaceutical, retail, and consumer goods. Apart from helping professionals understand vertical specific nuances, this book helps them to set both short-term goals for annual performance review and longer-term career planning. In addition, for a mid- or senior-level supply chain professional, the book offers ideas on ways to launch initiatives and demonstrate leadership to foster career growth. It offers ideas about unlocking new values for the organization and creating a data-driven decision support platform to gain financial efficiency for better management of CapEx and OpEx spend, thus improving the bottom line. The book includes a tool kit which includes operational data models, financial models, and presentation templates for creating and socializing proposals intended for cross-functional teams and demonstrating supply chain leadership. The book is divided into four major parts. In Part I, the book starts with an overview of key concepts in a manufacturing supply chain and procurement organization. It describes current forms of modern global supply chain and corporate procurement organizations. The objective of Part II is to provide a framework for a self-directed supply chain manager to understand how a large organization evaluates the contribution of supply chain managers and where it expects them to create value. To foster career growth as a supply chain professional, the book identifies six key knowledge pillars for demonstrating supply chain mastery: Technical and market knowledge of the end product and its constituents. Knowledge of internal product development and sustaining processes and supporting consumption data. Health and market condition of the supplier. Ability to create value. Ability to build internal and external executive relationships with key influencers. Ability to obtain best cost without compromising on quality and lead time. Negotiating cost, sourcing material, and then the logistics of moving the raw material through multiple stages and finally finished materials across the globe are some of the key areas which need continuous improvement. As a sentinel of efficiency, removing any kind of wastage leads to immediate value creation and contributes to the margin by improving the bottom line. In Part III, the book reviews twelve such verticals namely printer, medical, IT, energy, automotive, cloud, dairy, data management, avionics, biotech, apparel and start up and the supply chain nuances through the lenses of the framework created in Part II. In Part IV, the book goes back to focus on the professional growth of an individual supply chain person in an industry agnostic way. It provides examples of financial and operational efficiencies that a supply chain professional can create.- Resumé vydavatel
Description based upon print version of record.
3.6.4 Production (Operations in Service Companies).
Keywords: logistika (management); business logistics; elektronické knihy; kolektivní monografie; electronic books; collective monographs